Multimonth Prescription of Antiretroviral Therapy Among Children and Adolescents: Experiences From the Baylor International Pediatric AIDS Initiative in 6 African Countries. (15th August 2018) - Kim, Maria H.; Wanless, Richard S.; Caviness, Alison Chantal; Golin, Rachel; Amzel, Anouk; Ahmed, Saeed; Mhango, Joseph; Damba, David; Kayabu, Angelina; Chodota, Moses; Dlamini, Sandile; Chidah, Nodumo; et al.
Abstract : Background: To reach 90-90-90 targets, differentiated approaches to care are necessary. We describe the experience of delivering multimonth prescription (MMP) schedules of antiretroviral therapy (ART) to youth at centers of excellence in 6 African countries. Methods: We analyzed data from electronic medical records of patients aged 0–19 years started on ART. Patients were eligible to transition from monthly prescribing to MMP when clinically stable [improving CD4 +, viral load (VL) suppression, or minimal HIV-associated morbidity] and ART adherent (pill count 95%–105%). Patients were classified as transitioned to MMP after 3 consecutive visits at intervals of >56 days. We used survival analysis to describe death and lost to follow-up. We described adherence and acceptable immunologic response by CD4 + using 6-month and VL suppression (<400 copies per milliliter) using 12-month intervals. Results: Twenty-two thousand six hundred fifty-eight patients aged 0–19 years received ART and 14, 932 (66%) transitioned to MMP between 2003 and 2015. Of these 2.6% were lost to follow-up and 2.0% died. Median duration of MMP was 3.9 (interquartile range: 2.2–5.9) years. There were significant differences in survival ( P < 0.0001) between age groups, worst among those younger than 1 year and 15–19 years. The frequency of favorable clinical endpoints was high throughout the first 5 years of MMP, by year ranging from 87% to 94% acceptable immunologic response, 75% to 80% adherent, and 79% to 85% VL suppression. Conclusions: These analyses from 6 African countries demonstrate that youth on ART who transitioned to MMP overall maintained favorable outcomes in terms of death, retention, adherence, immunosuppression, and viral suppression. These results reassure that children and adolescents, who are clinically stable and ART adherent, can do well with reduced visit frequencies and extended ART refills. Abstract : Supplemental Digital Content is Available in the Text.